Anestezjologia i Intensywna Terapia Vasoplegic syndrome – current status - Kucewicz-Czech, Ewa; Puzio, Jacek; Zembala, Michał; Czech, Bronisław; Wojarski, Jacek; Maruszewski, Marcin; Knapik, Piotr (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2007)
Low systemic vascular resistance is a recognized complication of cardiopulmonary bypass and it is related to activation of an inflammatory response. A release of proinflammatory cytokines can cause a systemic inflammatory response contributing to generalized profound vasodilatation. Vasoplegia syndrome was defined using the following criteria: hypotension, low filling pressures, normal or elevated cardiac index, low peripheral resistance and metabolic acidosis. Low ventricular ejection fraction, preoperative ACE inhibitors and heparin use are the independent risk factors for the development of postoperative vasoplegia syndrome. Treatment of this syndrome requires the use of vasopressive agents but in some cases prolonged vasoplegia is resistant to norepinephrine. In these situations a single dose of methylene blue can restore systemic vascular resistance. When a dose no greater than 2 mg/kg is administered side effects do not occur. Methylene blue is a nitric oxide inhibitory drug which probably plays an important role in occurrence of vasoplegic syndrome.